(untitled) (Annals of Medical Research, 2021)
Aim: Postpneumonectomy empyema is one of the most difficult clinical conditions in thoracic surgery. There is a wide range of conventional treatment options ranging from tube thoracostomy, antibiotic irrigation to open-window thoracostomy. Vacuum-Assisted Closure (VAC) therapy is also among the treatment options. In our study we aimed to compare the outcomes and efficiency of conventional treatment procedures and VAC.Material and Methods: Eighteen male patients (average age 54.8± 18.68), who were diagnosed with postpneumonectomy empyema between July 2012 and November 2014, were divided into two groups. Nine patients (Group I) have been treated with conventional procedures, while the other nine patients (Group II) have been treated with VAC.Results: Five patients in the Group I were cured in an average of 9.6 months. Four patients underwent additional surgical intervention and they remained in the empyema clinic for 12 months in the follow-up period. Seven patients in the Group II were cured during the follow up period of an average of 14.8 months. Two patients who developed bronchopleural fistula remained in the empyema clinic. Average length of hospital stay is 109.3 days for the Group I and 63 days for the Group II. The treatment of the Group II has been found more successful than the Group I in terms of pain status assessment, patient’s comfort and postoperative cosmetic appearance.Conclusions: VAC group success rate has been found higher in terms patient’s comfort, the length of hospital stay and duration of empyema. Further studies are required to establish the success of this procedure.Keywords: Postpneumonectomy empyema; Vacuum-Assisted Closure (VAC); Thoracostomy.